Pertimbangan Hakim Dalam Menetapkan Itsbat Nikah di PA Bekasi (Studi Analisis Nomor 010/Pdt.P/2018/PA.Bks). - -, Afifuddin; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
This study describes the procedure for requesting a marriage determination at the Bekasi ReligiousCourt, as well as analyzing judges’ considerations in deciding a marriage determination case. Thisresearch is a field research, using descriptive methods. To find the results of this study, the researcherstook several steps, namely data collection, data processing, data analysis, and drawing conclusions.From the results of this study it can be concluded that the judges considerations refer to, 1) LawNumber 1 Year 1974 Article 2. 2) Government Regulation Number 9 Year 1975. 3) Articles 14 and7 paragraph 3 letter E Compilation of Islamic Law. 4) the book “I’anatut Tholibin volume 10, page254. In addition, the Judge is also flexible in seeing other factors for the benefit and legal certaintyof the petitioners. The procedure for requesting a marriage determination at the Bekasi ReligiousCourt is the same as the procedure for filing other cases, which are registered at the Religious Court.What distinguishes only the Application Conditions. Meanwhile, the results of the case of marriagedetermination that have been signed (with permanent legal force) can be used as evidence for theparties to register and register their marriage with the Marriage Registration Officer (PPN), at theOffice of Religious Affairs where the husband and wife live.